The influence of sleep on language production modalities in preschool children with Down syndrome. (14th June 2020) - Arias‐Trejo, Natalia; Angulo‐Chavira, Armando Quetzalcóatl; Demara, Bianca; Figueroa, Carlos; Edgin, Jamie
Abstract: Evidence suggests that sleep may relate to oral language production in children with Down syndrome. However, these children are capable of using complex referential gestures as a compensation strategy for problems with oral production, and those with a greater productive oral vocabulary have less gestural vocabulary. The goal of this study was to explore whether sleep quality relates to oral and gestural production modalities in children with Down syndrome. We evaluated 36 preschool children with and without Down syndrome, paired by chronological age and gender, with similar sociodemographic backgrounds, using actigraphy to measure sleep behaviour and the Communicative Development Inventory for Down syndrome to measure vocabulary. Children with Down syndrome with better sleep efficiency showed more oral production but less gestural production. These results highlight the importance of sleep quality to language learning in children with Down syndrome.